Multi-objective green mixed vehicle routing problem under rough environment - Dutta, Joydeep; Barma, Partha Sarathi; Mukherjee, Anupam; Kar, Samarjit; De, Tanmay; Pamučar, Dragan; Šukevičius, Šarūnas; Garbinčius, Giedrius (Transport, 2022)
This paper proposes a multi-objective Green Vehicle Routing Problem (G-VRP) considering two types of vehicles likely company-owned vehicle and third-party logistics in the imprecise environment. Focusing only on one objective, especially the distance in the VRP is not always right in the sustainability point of view. Here we present a bi-objective model for the G-VRP that can address the issue of the emission of GreenHouse Gases (GHGs). We also consider the demand as a rough variable. This paper uses the Non-Dominated Sorting Genetic Algorithm II (NSGA-II) to solve the proposed model. Finally, it uses Multicriteria Optimization and Compromise Solution (abbreviation in Serbian – VIKOR) method to determine the best alternative from the Pareto front.First published online 25 February 2021